decomposition of 2-propanol over Alumina supported Thoria and Potassium ion modified catalysts - Bukhzam, A.; Benhmid, A.; Edbey, K.; Elsahli, S.; Mekhemer, G.A.H.; Zaki, M. I. (Libyan Journal of Science &Technology, 2022)
A series of alumina and K ion-modified supported thoria catalysts were prepared using thorium nitrate hexahydrate at different loading levels (320 wt% of thoria) by the impregnating method. The decomposition of 2 propanol on the surface of these catalysts was investigated. Pure g-alumina catalyst shows low activity and higher selectivity towards dehydration reaction. In contrast, thoria catalyst shows low activity and higher selectivity towards dehydrogenation reaction. The activity and selectivity of alumina supported thoria catalyst towards dehydrogenation reaction was increased with increasing the amount of O2 on g-alumina. However, the activity and selectivity of these catalysts towards dehydration reaction were observed to be decreased with increasing the amount of O2. The surface of the dehydrogenation reaction of 2propanol was increased with increasing the addition of K ion on the surface of alumina-supported thoria catalysts.